Judicial Discovery of Law in Normative Gaps of Contemporary Medical Case - Muhammad Abdulhamid; Ria Agustina; Kamal Anas; Meri Lidiawati; Dhira Taramadia Westiartika (IHSA Institute, 2026)
The rapid evolution of medical technology increasingly outpaces the parameters of ethical-legal frameworks regarding passive euthanasia, genetic data sourcing and processing, and digital informed consent, thereby creating significant legal lacunae that engender profound ethical-legal dilemmas. When statutory provisions offer no explicit guidance, judges are compelled to resort to rechtsvinding, the construction of law through interpretative, analogical, and creative application of sub-statutory measures available to them. This legal research aims to assess the mechanisms and methodologies employed by judges to utilize rechtsvinding in bridging systemic functional deficiencies in law as applied to medical malpractice. Using conceptual-analytical methods supported by case study approaches, this research investigates issues of patient autonomy, medical beneficence, and the medical practitioner's legal duty of care in precluding harm, through analysis of multiple court decisions. The findings demonstrate that judicial integration of medical ethical principles becomes a predominant factor when medical law remains silent across numerous legal domains relevant to medical malpractice adjudication. Ultimately, this facilitates the development of a more robust health legislative framework wherein judicial practice addresses specific substantive problems and expands the scope of medical law. This research substantiates the claim that rechtsvinding functions as a critical instrument for protecting public health in the construction and development of law.